Determinación de la respuesta de cuatro enraizantes aplicados sobre la semilla de maíz (Zea maíz) del hibrido dekalb 7088 en época lluviosa en la zona de Febres Cordero - Los Ríos. - Bayas Silva, Mónica Del Carmen (2014)
The research was conducted in the area of Mata de Cacao, Febres Cordero Parish, Canton Babahoyo, Los Rios Province in hybrid maize 'Dekalb 7088' enraizantes Maz Root (3.0 and 4.0 l / ha). Espigold (1.5 and 3.0l / ha), phytoactive (0.4 and 0.6 l / ha) and Green Master (2.0 and 3.0l / ha); plus a control treatment without rooting and unfertilized without rooting included; giving a total of 10 treatments. The completely randomized design (DBCA) blocks in four replications. The variables were evaluated: root length; wet and dry weight of root; wet and dry weight of leaf area and number of leaves at 7; 14 and 21 days after planting; days to male and female flowering; cob insertion height and plant; leaf area index; number of plants and harvested ears; percentage of plants with root lodging and stalk; length and weight of roots at harvest; diameter and ear length; rows of kernels per ear; kernels per ear; weight of 100 grains; relationship grain - cob and grain yield. The results show that with treatment (T6) phytoactive 0.6 l / ha, longer roots at harvest was achieved, exceeding by 24.14% to control without rooting. Treatments (T8) Green Master 3.0l / ha and (T4) Espigold 3.0l / ha obtained the highest grain yields 8.5 and 8.43 t / ha, exceeding 13.73% and 13.46% to the control (T9) devoid of rooting, respectively. All treatments that include enraizantes bioestimulantes presented positive response in grain in the range of 9.86% to 13.73%, compared to the control lacking the rooting. The hybrid 'Dekalb 7088' fertilized achieved an increase of 39.14% compared to unfertilized.